MENYIBAK AJARAN SOSIAL GEREJA PAUS FRANSISKUS DI MASA PANDEMI DALAM PERSPEKTIP HIDUP SOSIAL SEBAGAI RUMAH BERSAMA - Benedikta Yosefina Kebingin (STP Reinha Larantuka, 2021)
This research is intended to examine the social teachings of the Church of Pope Francis during the pandemic. It is interesting to study because the social teachings of the Church which has been rolling from time to time since 1891 covers documents classified as the social teachings of the Church; while the catechesis of Pope Francis during the pandemic in nine themes was directly entitled